Study of knowledge, attitude, and practices of biomedical waste management among healthcare workers in tertiary care government hospital in western Maharashtra - Gawande, Abhishek A.; Gokhale, Ramakant M.; Soni, Akhil A.; Ram, Nithes (International Journal Of Community Medicine And Public Health, 2022)
Background: Bio-medical wastes produced in the course of health care activities has a higher potential for infection and injury than any other type of waste among healthcare workers. Studies in India and other developing countries have shown lack of knowledge and poor practice of biomedical waste (BMW) management. Methods: This was an observational hospital-based cross-sectional study. Study group included 210 healthcare workers, which includes doctors, interns, nursing staff, laboratory technicians, and class IV workers. Study was done by using a semi-structured questionnaire. The data was analysed using Microsoft Excel 2016. Results: The majority of doctors (92%), interns (90%), nursing staff (93%) had adequate knowledge about BMW management, but lab technicians and class IV workers (70%) had poor knowledge. Among all health care workers (HCW), 50% of HCW attended the training for biomedical waste management, 46% of the HCW thought that BMW management is an extra burden on work. Except for nursing staff (100%), other healthcare workers (>55%) do not follow the color-coding of BMW. Conclusions: The study emphasizes the need to conduct periodic training among all healthcare workers about all aspects related to bio-medical waste management.